Analysis of Innovation Modes in the Russian Economy: Methodological Approaches and First Results - Leonid Gokhberg; Tatiana Kuznetsova; Vitaliy Roud (Foresight and STI Governance, 2010)
The paper discusses methodologies used to adapt to the Russian context the usual measures of STI performance, developed and implemented under the framework of the European Manufacturing Survey (EMS), and reports on results. Two rounds of surveys were conducted in 2009-2010 covering around 2000 Russian companies. The third round is planned for 2012.  The paper outlines how innovative activities in the real sector of the Russian economy can be measured.